Development of a multiplex PCR assay for the identification of eight species members of the Thai Hyrcanus Group (Diptera: Culicidae) - Chayanit Hempolchom (2018)
The Hyrcanus Group comprises important vectors of malaria because of Plasmodium vivax Grassi and Feletti and filariasis caused by Brugia malayi Brug in many countries of South, Southeast and East Asian regions. In Thailand, eight species members (Anopheles argyropus Swellengrebel, An. crawfordi Reid, An. nigerrimus Giles, An. nitidus Harrison, Scanlon & Reid, An. paraliae Sandosham, An. peditaeniatus Leicester, An. pursati Laveran and An. sinensis Wiedemann) of the Hyrcanus Group have been recognized. Due to morphological overlap, adult females of the Hyrcanus Group in Thailand have been misidentified markedly among the eight species, particularly when using the traumatic scales of wild-caught specimens from epidemiology and control approaches. Therefore, this study first developed a simple and robust multiplex PCR assay, based on second internal transcribed spacer sequences of ribosomal DNA, for differentiating the eight species members of the Thai Hyrcanus Group. © 2013 The Japanese Society of Applied Entomology and Zoology.